Topological Quantum Computation Using Majorana Fermions in Nanowire Networks: A Theoretical Feasibility Study - Loso Judijanto; Khalil Zaman; Zara Ali (Yayasan Adra Karima Hubbi, 2026)
Topological quantum computation offers a promising pathway toward fault-tolerant quantum information processing, with Majorana fermions emerging as key quasiparticles capable of encoding quantum states protected from local decoherence. Nanowire networks engineered to host Majorana zero modes have been widely proposed, yet their practical feasibility requires rigorous theoretical assessment under realistic physical constraints. This study aims to evaluate the theoretical viability of implementing topological quantum computation using Majorana fermions in semiconductor–superconductor nanowire networks. A modeling framework incorporating Bogoliubov–de Gennes equations, topological phase diagrams, non-Abelian braiding protocols, and disorder-induced perturbations is employed to assess stability and control requirements. Simulations investigate parameter regimes involving magnetic field strength, spin–orbit coupling, proximity-induced superconductivity, and wire-junction geometries. The results show that stable Majorana modes can be achieved within narrow but experimentally accessible parameter windows, and that non-Abelian braiding operations remain topologically robust against moderate disorder and quasiparticle poisoning. The study concludes that while significant engineering challenges persist—particularly regarding temperature constraints, material uniformity, and junction coherence—Majorana-based topological quantum computation remains theoretically feasible with current technological progress.